Detection and isolation of disseminated tumor cells in bone marrow of patients with clinically localized prostate cancer. Issue 14 (26th August 2019) - Cackowski, Frank C.; Wang, Yugang; Decker, Joseph T.; Sifuentes, Christopher; Weindorf, Steven; Jung, Younghun; Wang, Yu; Decker, Ann M.; Yumoto, Kenji; Szerlip, Nicholas; Buttitta, Laura; Pienta, Kenneth J.; et al.
Abstract: Background: Disseminated tumor cells (DTCs) have been reported in the bone marrow (BM) of patients with localized prostate cancer (PCa). However, the existence of these cells continues to be questioned, and few methods exist for viable DTC isolation. Therefore, we sought to develop novel approaches to identify and, if detected, analyze localized PCa patient DTCs. Methods: We used fluorescence‐activated cell sorting (FACS) to isolate a putative DTC population, which was negative for CD45, CD235a, alkaline phosphatase, and CD34, and strongly expressed EPCAM. We examined tumor cell content by bulk cell RNA sequencing (RNA‐Seq) and whole‐exome sequencing after whole genome amplification. We also enriched for BM DTCs with α‐EPCAM immunomagnetic beads and performed quantitative reverse trancriptase polymerase chain reaction (qRT‐PCR) for PCa markers. Results: At a threshold of 4 cells per million BM cells, the putative DTC population was present in 10 of 58 patients (17%) with localized PCa, 4 of 8 patients with metastatic PCa of varying disease control, and 1 of 8 patients with no known cancer, and was positively correlated with patients' plasma PSA values. RNA‐Seq analysis of the putative DTC population collected from samples above (3 patients) and below (5 patients) the threshold of 4 putative DTCs per million showed increased expression of PCa marker genes in 4 of 8 patients with localized PCa, but not the one normal donor who had the putative DTC population present. Whole‐exome sequencing also showed the presence of single nucleotide polymorphisms and structural variants in the gene characteristics of PCa in 2 of 3 localized PCa patients. To examine the likely contaminating cell types, we used a myeloid colony formation assay, differential counts of cell smears, and analysis of the RNA‐Seq data using the CIBERSORT algorithm, which most strongly suggested the presence of B‐cell lineages as a contaminant. Finally, we used EPCAM enrichment and qRT‐PCR for PCa markers to estimate DTC prevalence and found evidence of DTCs in 21 of 44 samples (47%). Conclusion: These data support the presence of DTCs in the BM of a subset of patients with localized PCa and describe a novel FACS method for isolation and analysis of viable DTCs.